Comparing the effect of kinesio taping versus manual trigger release on thenar eminence pain in professional palestrato - SURESH.T.N; P.SRAVAN BABU (International Journal of Pharma and Bio Sciences, 2019)
The muscles of thumb are the most flexible of all digits, which allow to movement in various direction. Thenar eminence pain is caused when the thumb is subjected to repetitive functions which leads to their overuse over a period of time which makes it tired. This pain is often is commonly reported by regular gym goers. Thenar eminence pain affects daily gym activity. It gets triggered during weight lifting and when dumb bells are used during workout. When overused, this part gets inflamed and results in thenar eminence pain. The ability to catch and grip may be compromised or lost. Tasks requiring agility and control such as bench press, double bar, and other weight lifting activities become difficult and frustrating because of muscle weakness and loss of fine motor control. This study aims at comparing the kinesio taping technique and manual trigger release for thenar eminence pain among professional gym goers and also at finding out which is the better of the two techniques and give results according to it. It is an experimental study done on 30 male subjects, who have the experience of going to gym for 3or above months. 10 subjects are included in to Group-A tapping and 10 subjects in Group-B trigger release and 10 subjects in Group-c control group. Visual analogue scale both pre and posttest were taken and calculated for obtaining results. Group A is more statistically significant than group B and group C. That is kinesio tapping is significant in reducing pain than the manual trigger release technique.